Antidiabetic potential of the isolated fractions from the plants of Rosaceae family in streptozotocin-induced diabetic rats - Gholamreza Bahrami; Babak Izadi; Seyed Shahram Miraghaee; Bahar Mohammadi; Razieh Hatami; Soraya Sajadimajd; Nasim Batooie (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Diabetes is a group of multifactorial disorders characterized by chronic-elevated blood glucose levels (hyperglycemia). Natural remedies are used as alternative medications to treat diabetes. Here, we tested the protective effect of the plant extracts of the Rosaceae family on improving insulin secretion and repairing the pancreatic beta cells in diabetic rats. Experimental approach: The oligosaccharide fraction was isolated from the Rosaceae family of herbs. LC-MS/MS was applied to characterize the isolated fractions. The male Wistar rats were randomly divided into six groups, 10 each, including the control group with no intervention, diabetic rats without treatment, diabetic rats that received the extract of Malus domestica (apple), Cydonia oblonga (quince), Prunus persica (nectarine), and Prunus persica (peach), separately. Rats were monitored for the weight, fasting plasma glucose, and insulin levels. The effect of extracts in streptozotocin (STZ)-induced diabetic rats on the pancreatic islets was evaluated by morphometric analysis. Findings/Results: LC-MS/MS results indicated a similar mass spectrum of isolated fractions from nectarine and peach with Rosa canina. Oral administration of nectarine and peach extracts to STZ-induced diabetic rats showed restoration of blood glucose levels to normal levels with a concomitant increase in insulin levels. Morphometric analysis of pancreatic sections revealed the increase in number, diameter, volume, and area of the pancreatic islets in the diabetic rats treated with extracts compared to the untreated diabetic rats. Conclusion and implications: Nectarine and peach extracts' anti-diabetic properties improved insulin secretion and pancreatic beta-cell function and subsequently led to restoring pancreatic islet mass in STZ-induced diabetic rats.